2015, unprecedented successes of the OPQ in international competitions - Chong Cáceres, Miguel (2015)
2015, a year in which we commemorate the 20th anniversary of the Peruvian Chemistry Olympiad (OPQ), has been a very successful year for our Olympic team in the international Chemistry events in which Peru has participated. Three medals were obtained in the International Chemistry Olympiad (IChO) and four were awarded to our team at the Iberoamerican Chemistry Olympiad (OIAQ). Moreover, in the latter a student from our delegation had the best final score. Our national competition, the Peruvian Chemistry Olympiad (OPQ), had a great success with regard to student participation (more than two thousand students registered nationwide) making it an unmissable event among secondary school students interested in Chemistry.